The coastal landslides of Shetland. (3rd April 2018) - Ballantyne, Colin K.; Dawson, Sue; Dick, Ryan; Fabel, Derek; Kralikaite, Emilija; Milne, Fraser; Sandeman, Graeme F.; Xu, Sheng
ABSTRACT: Little is known of hard-rock coastal landsliding in Scotland. We identify 128 individual coastal landslides or landslide complexes >50 m wide along the coasts of Shetland. Most are apparently translational slides characterized by headscarps, displaced blocks and/or debris runout, but 13 deep-seated failures with tension cracks up to 200 m inland from cliff crests were also identified. Thirty-one sites exhibit evidence of at least localized recent activity. Landslide distribution is primarily determined by the distribution of coastal cliffs >30 m high, and they are preferentially developed on metasedimentary rocks. Analysis of 16 landslides on Fetlar (NE Shetland) indicates that most are translational dip-slip failures; 3 represent deep-seated failures and several exhibit active frontal erosion attributable to basal sapping by storm waves. As these landslides terminate in shallow water, failure was probably initiated when rising sea level resulted in footslope erosion and upslope propagation of instability, causing downslope displacement of landslide blocks on upper slopes. 10 Be exposure dating of two headscarps yielded ages of 4.8 ± 0.2 ka and 4.4 ± 0.2 ka, consistent with the onset of footslope erosion as sea level rose. Our results suggest that landslides have played a hitherto undocumented but important role in retreat of cliffed coastlines in Scotland.